Assessment of the body development kinetic of broiler breeders by non-invasive imaging tools. (9th April 2019) - Grandhaye, Jérémy; Lecompte, François; Staub, Christophe; Venturi, Eric; Plotton, Ingrid; Cailleau-Audouin, Estelle; Ganier, Patrice; Ramé, Christelle; Brière, Sylvain; Dupont, Joelle; Froment, Pascal
ABSTRACT: In order to determine the body composition of parental broilers during growth from hatching to adulthood (32 wk of age), we evaluated the kinetics of fattening, growth rate, reproduction parameters, and body composition of the animals by using non-invasive tools such as medical imaging (ultrasound and CT scan) and blood sample analysis. The use of CT scanner allowed us to monitor the development of the body composition (fatness, bone, muscle, ovary, and testis growth) of these same animals. These analyses were accompanied by biochemical blood analyses such as steroids, metabolites, and some adipokines concentration. Difference in the body composition between males and females appeared at 16 wk of age. From 20 wk of age, shortly before the onset of lay, the females had 1.6-fold more adipose tissues than males ( P < 0.001) and 8-fold more elevated plasma triglycerides levels. In addition, females, from 16 wk of age, presented a weakened bone quality in comparison to males ( P < 0.001). The ratio of the tibia volume/tibia length was 33.2% lower in female compared to male chicken at 32 wk of age ( P < 0.001). However, the pectoral muscle had the same volume in both sexes. The production of steroids by gonad started at 16 wk of age for both sexes, and the testis and ovary development could be measured by imaging tools at 24 wk. The follicle development was correlated to the ovarian fat tissue (r = 0.80) and fatness. In conclusion, the use of CT scanner and ultrasound system has allowed investigate the body composition of live animals and actual parental breeds with to the aim of using them for genetic selection.